A Global-Middle-Class House?1 Cultural Capital, Taste, and Kitsch. (4th May 2018) - Levin, Iris
Abstract: In this article, I show how the category of the migrant house, as has been recently discussed in much scholarship, can be expanded to include another subcategory—the global-middle-class house. Recently, the migrant house has generated much research in migration studies and in disciplines of the built environment. Consequently, it has been examined through various perspectives, including home and belonging, materiality in the home, and the transnational home. It has not been examined, however, through the concepts of cultural capital, taste and kitsch, as developed by Bourdieu and others. This article applies these concepts in the exploration of the migrant house through a case study of one house and its transformation from old to new in suburban Melbourne. The article shows how the concepts of cultural capital, taste and kitsch can be utilized to expand the category of the migrant house to include the global-middle-class house. Following a theoretical discussion, the article analys es the old family house, the decision to demolish, the construction process and the redevelopment of a new house, together with an analysis of material objects in the new house and around it. The article argues that this is a specific kind of a migrant house, a global-middle-class house, because it combines popular global taste with objects taken from the ancestral past of its migrant residents.